Inducing targeted failure in cadaveric testing of 3-segment spinal units with and without simulated metastases. (January 2018) - Groenen, Karlijn H.J.; Janssen, Dennis; van der Linden, Yvette M.; Kooloos, Jan G.M.; Homminga, Jasper; Verdonschot, Nico; Tanck, Esther
Highlights: A method to induce targeted failure in 3-segment spinal units is proposed. A method to capture specimens' deformation in the post-failure state is proposed. An adequate failure criterion is important in testing 3-segment spinal units. Abstract: We propose an experimental setup and protocol able to induce targeted failure of the middle vertebra in 3-segment spinal units and to capture the specimens' deformation in their post-failure state. Sixteen 3-segment spinal units with and without artificial metastases were destructively tested in axial compression using one of two failure criteria; either: (A) A clear drop in force (>10–15% of peak force) (n = 4); or (B) A minimum displacement of 5 mm (n = 12). Subsequently, the specimens were fully fixated in polymethylmethacrylate (PMMA), thereby preserving their post-failure state. Pre- and post-experiment computed tomography (CT) scans were acquired to determine the occurrence of failure in one of the vertebral bodies. All specimens were successfully fixated in their post-failure state. When applying failure criterion A, two specimens showed signs of failure. When applying failure criterion B, all specimens showed signs of failure; in 9 out of 12 specimens this occurred in the middle vertebrae only. In conclusion, this research provides an experimental setup and protocol able to induce targeted failure of 3-segment spinal units and to capture the specimens' deformation in their post-failure state. Furthermore, this study illustrates the importance of an adequate failure criterion for successful simulation of vertebral fractures in an experimental setup.